At the Heart of Learning (Series: Paper 1 of 4): Putuna Kulini: The trouble with "Hearing". Issue 1 (March 2014) - Osborne, Sam
Remote Indigenous school principals find themselves caught in the middle of system priorities and demands, the demands of running complex and busy local schools, and the expectations and needs of the local community. Remote communities often complain that they are not being listened to or "heard", but the process of listening, hearing and understanding in the complex cultural context of remote Aboriginal communities is far more complex than a visit or a single conversation can achieve. This paper examines the clash between values, perspectives and worldviews that is played out on a daily basis as schools go about their business of educating whilst also attempting to take account of what is important for the communities they work in. This work highlights the need for remote principals and educators to reposition themselves in the dialogue with communities in order to allow room for a new conversation that gets to the "heart of learning".